Language planning and policy : issues in language planning and literacy - Liddicoat, Anthony, 1962- (Language planning and policy., 2007)
While literacy has always been central to language planning work, there are fewer studies which focus primarily on literacy as a language planning activity. This volume investigates the complex issues and social and political pressures relating to literacy in a variety of language planning contexts around the world.